Morphological description of the fourth instar larva: Culicoides cataneii and Culicoides sahariensis (Diptera: Ceratopogonidae) - Slama, Darine; Khedher, Asma; Bdira, Sassi; Khayech, Fethi; Delecolle, Jean-Claude; Mezhoud, Habib; Babba, Hamouda; Emna, Chaker (Zootaxa, 2013)
This study was carried out of the region of Monastir in Central Tunisia, between July and August 2010. Larvae were col-lected using a floatation technique with magnesium sulfate in mud samples. The fourth instar larva of Culicoides cataneii Clastrier, 1957 and Culicoides sahariensis Callot, Kremer, Bailly-Choumara, 1970 are described, illustrated and drawn. Measurements of instars IV are also presented. This is the first record of Culicoides cataneii and Culicoides sahariensis (Diptera: Ceratopogonidae) to Tunisia.